Characterizing Droughts During the Rice Growth Period in Northeast China Based on Daily SPEI Under Climate Change - Tangzhe Nie; Xiu Liu; Peng Chen; Lili Jiang; Zhongyi Sun; Shuai Yin; Tianyi Wang; Tiecheng Li; Chong Du (Plants)
In agricultural production, droughts occurring during the crucial growth periods of crops hinder crop development, while the daily-scale standardized precipitation evapotranspiration index (SPEI) can be applied to accurately identify the drought characteristics. In this study, we used the statistical downscaling method to obtain the daily precipitation (Pr), maximum air temperature (Tmax) and minimum air temperature (Tmin) during the rice growing season in Heilongjiang Province from 2015 to 2100 under the SSP1-2.6, SSP2-4.5 and SSP5-8.5 in CMIP6, to study the spatial and temporal characteristics of drought during the rice growing season in cold region and the effect of climate change on drought characteristics. The potential evapotranspiration (PET0) was calculated using the regression correction method of the Hargreaves formula recommended by the FAO, and the daily SPEI was calculated to quantitatively identify the drought classification. The Pearson correlation coefficient was used to analyze the correlation between the meteorological factors (Pr, Tmax, Tmin), PET0 and SPEI. The results showed that: (1) Under 3 SSP scenarios, Pr showed an increasing trend from the northwest to the southeast, Tmax showed an increasing trend from the northeast to the southwest, and higher Tmin was mainly distributed in the east and west regions. (2) PET0 indicated an overall interannual rise in the three future SSP scenarios, with higher values mainly distributed in the central and western regions. The mean daily PET0 values ranged from 4.8 to 6.0 mm/d. (3) Under SSP1-2.6, rice mainly experienced mild drought and moderate drought (−0.5 ≥ SPEI > −1.5). The predominant drought classifications experienced were mild, moderate, and severe drought under SSP2-4.5 and SSP8.5 (−0.5 ≥ SPEI > −2.0). (4) The tillering stage experienced the highest drought frequency and drought intensity, with the longest drought lasting 24 days. However, the heading flower stage had the lowest drought frequency and drought intensity. The drought barycenter was mainly in Tieli and Suihua. (5) The PET0 was most affected by the Tmax, while the SPEI was most affected by the Pr. This study offers a scientific and rational foundation for understanding the drought sensitivity of rice in Northeast China, as well as a rationale for the optimal scheduling of water resources in agriculture in the future.